Prevalence and Identification of Scalp Fungal Infections in Primary School Pupils - Huntush, Dr. Zina Saleam (Journal of Science in Medicine and Life, 2025)
Background Dermatophytes, a group of fungi, are known to infect keratinized tissues in humans and animals, causing dermatophytosis. These infections, especially in the scalp, can result in various clinical symptoms, impacting the health and well-being of individuals, particularly primary school pupils. Understanding the fungal species responsible for such infections is crucial for effective management and prevention Purpose This study aimed to investigate the prevalence of fungal and yeast species causing scalp infections in primary school pupils and identify the specific species responsible for these infections. By understanding the types of fungi involved, we can better inform strategies for early diagnosis, treatment, and prevention Methods A total of 60 hair samples were collected from primary school pupils aged 8 to 11 in Shatrah district, Al-Shatra city. These samples were carefully processed and analyzed in a microbiology laboratory using standard techniques. Fungal species were identified based on cultural and morphological characteristics, and taxonomic keys from various references were employed to ensure accurate classification Results The research identified 25 fungal species belonging to 24 genera. Notably, Aspergillus was found to be the most prevalent species, followed by Penicillium and several others. The study revealed variations in fungal prevalence between male and female pupils, with implications for personal hygiene and environmental factors contributing to the differences Implications for Practice Understanding the prevalence of scalp fungal infections and the specific species involved is essential for health practitioners, school authorities, and parents. This knowledge can inform proactive measures to prevent the spread of these infections, such as improving personal hygiene and minimizing contact with animals and soil. Early diagnosis and appropriate treatment can reduce the impact of these infections on the affected pupils.